2013
DOI: 10.1186/1742-4682-10-13
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of the effects of lead poisoning on the intelligence and neurobehavioral abilities of children

Abstract: BackgroundLead is a heavy metal and important environmental toxicant and nerve poison that can destruction many functions of the nervous system. Lead poisoning is a medical condition caused by increased levels of lead in the body. Lead interferes with a variety of body processes and is toxic to many organs and issues, including the central nervous system. It interferes with the development of the nervous system, and is therefore particularly toxic to children, causing potentially permanent neural and cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 30 publications
0
54
0
3
Order By: Relevance
“…However, lead exposure, even at low concentration, can cause metabolic disorder of other metallic elements in the body [8,16,17]. Some studies found that elevated BLL will decrease the plasma concentration of Fe, Ca and other nutritional metallic elements [18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, lead exposure, even at low concentration, can cause metabolic disorder of other metallic elements in the body [8,16,17]. Some studies found that elevated BLL will decrease the plasma concentration of Fe, Ca and other nutritional metallic elements [18].…”
Section: Introductionmentioning
confidence: 98%
“…Environmental lead exposure, affecting both adults and children, is increasingly becoming a healthy concern [2,3]. Pb enters into the body mainly through the respiratory system and the digestive tract, and causes a series of documented adverse effects particularly in the nervous systems [4][5][6], such as developmental delays, insomnia, irritability, tremors, hearing loss, deficits in behavioral functioning, impaired cognitive and learning abilities, and social withdrawal [7][8][9]. Since children have underdeveloped and inadequate blood brain barrier, unrestricted Pb accumulation in the brain will eventually disrupt neural signal transduction and irreversibly damage the nervous system [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Post hoc analysis Tukey's analysis was done and P values were expressed showing significance difference of data. [22]. Lead accumulates in the environment and contaminates the water, soil, air and food chain leading to human diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that increased blood lead levels in young children are associated with neurobehavioral and cognitive abilities (Hou et al, 2013) including lower reading readiness (McLaine, et al, 2013) and lower 4 th grade reading and math scores (Miranda et al, 2007). Assessing and preventing lead exposures are often overlooked in rural communities but are important to rural children's learning ability.…”
Section: Introductionmentioning
confidence: 99%